2022
DOI: 10.3390/pharmaceutics14030602
|View full text |Cite
|
Sign up to set email alerts
|

The Poly-Histidine Tag H6 Mediates Structural and Functional Properties of Disintegrating, Protein-Releasing Inclusion Bodies

Abstract: The coordination between histidine-rich peptides and divalent cations supports the formation of nano- and micro-scale protein biomaterials, including toxic and non-toxic functional amyloids, which can be adapted as drug delivery systems. Among them, inclusion bodies (IBs) formed in recombinant bacteria have shown promise as protein depots for time-sustained protein release. We have demonstrated here that the hexahistidine (H6) tag, fused to recombinant proteins, impacts both on the formation of bacterial IBs a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 72 publications
1
15
0
Order By: Relevance
“…Moreover, it also indicated that histidine residues within the hybrid tag were available for cation-mediated microparticle organization, in a fully reversible process. This observation is important as the formation of Zn-mediated microparticles results in highly interesting artificial materials, which, like bacterial inclusion bodies, , show protein-leaking properties. , Then, mimicking metal-based amyloid fibers, Zn-mediated protein-only microparticles represent promising slow protein delivery systems for the in vivo administration of protein drugs. , Therefore, the His–Cys hybrid tag proposed here not only assisted in nanoparticle formation through covalent disulfide bridge formation but also assisted in protein clustering as microscale granules upon the addition of cationic Zn from an external source. Both assembling mechanisms, reversible by either reducing agents or EDTA, offer an unexpected versatility to the protein material resulting from H3C-tagged building blocks.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, it also indicated that histidine residues within the hybrid tag were available for cation-mediated microparticle organization, in a fully reversible process. This observation is important as the formation of Zn-mediated microparticles results in highly interesting artificial materials, which, like bacterial inclusion bodies, , show protein-leaking properties. , Then, mimicking metal-based amyloid fibers, Zn-mediated protein-only microparticles represent promising slow protein delivery systems for the in vivo administration of protein drugs. , Therefore, the His–Cys hybrid tag proposed here not only assisted in nanoparticle formation through covalent disulfide bridge formation but also assisted in protein clustering as microscale granules upon the addition of cationic Zn from an external source. Both assembling mechanisms, reversible by either reducing agents or EDTA, offer an unexpected versatility to the protein material resulting from H3C-tagged building blocks.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the adverse effects could also derive form the lack of biological neutrality of the antibody scaffold that interacts with Fc receptors expressed on normal cells (off-target effect) (Criscitiello et al, 2021;Wilkinson et al, 2021). In addition, both particular nanomedical approaches have been extensively reviewed, also by us (Sanchez-Garcia et al, 2016;Serna et al, 2018), and are out of the scope of the present review that focuses on the plain scaffolding uses of proteins in clinics.…”
Section: Single Polypeptides As Plain Drug Carriersmentioning
confidence: 99%
“…Inclusion bodies formed by growth factors such as the human FGF-2, the Mexican axolotl lipoxygenase and others offer a combination of mechanical and biological stimuli favoring among other effects, wound healing (Seras-Franzoso et al, 2014;Stamm et al, 2018). This is because the forming protein is slowly released under physiological conditions through a slow self-disintegrating process (Cespedes et al, 2020;Sánchez et al, 2022), and therefore, the functional building blocks are available for biological activities. Synthetic versions of inclusion bodies, fabricated in vitro from pure protein (Alamo et al, 2021b;López-Laguna et al, 2021;Sanchez et al, 2020), offer friendly versions of such functional topographies (Serna et al, 2020).…”
Section: Protein Scaffolds For Complex Materials In Tissue Engineerin...mentioning
confidence: 99%
“…Therefore, LIRFP CD QIT-MS could be a rapid method to evaluate PHB production during bacterial culture without using toxic chemicals in processing bacterial samples. Moreover, LIRFP CD QIT-MS might be also applied to measure the uptake of heavy metals (e.g., Cd 2+ and Pb 2+ ) in marine lactic acid bacteria and inclusion bodies formed in recombinant bacteria …”
mentioning
confidence: 99%
“…Moreover, LIRFP CD QIT-MS might be also applied to measure the uptake of heavy metals (e.g., Cd 2+ and Pb 2+ ) in marine lactic acid bacteria 27 and inclusion bodies formed in recombinant bacteria. 28 ■ ASSOCIATED CONTENT * sı Supporting Information…”
mentioning
confidence: 99%